#TITLE_ALTERNATIVE# - HIDAYATULLAH (NIM 12203050), NOR
There is a finite volume of hydrocarbons that can be produced economically from any wells, field, or reservoir, which referred to as ultimate recovery and is equal to the reserve before production commences. As hydrocarbons are produced, reserves will decline as cumulative production increase, but the sum of cumulative production and reserves always equal the estimated ultimate recovery at that time. The ultimate recovery itself change as production performance evaluated along the production life until it reach at some point where the well must be ceased as the production no longer economically profit. When the production of the well must be ceased is an important to know. In most cases, production will be abandoned before it would ceased due to natural cause. It is considered because production will decline to a rate at which its cost more to produce hydrocarbon than those the hydrocarbon are worth which known as the economic limit. At the economic limit, the production cost are equal to the value of the produced hydrocarbon, to continue the production beyond this point will cause economic loss. There are many factor which effect the rate at which hydrocarbon produced from a well or a reservoir. Geologic factor, i. e, characterictic of the rock, depth, thickness, natural reservoir energy, and reservoir fluid characteristic are the factor that have significant effect. But its alter need more time in result of its effect couldn’t be instantaneous. The other important factor is global market mechanism which implicitely discribed as hidrocarbon price and cost conducted due to production activity. The government regulation factor, and the contract system conducted is one of ultimate factor that have significant effect. In this paper will reveal the equation model derivation of economic limit for production sharing contract that prevail in Indonesia, also sensitivity analysis of influent variables which related to evaluation of contract system prevailed.